Identification of Sound Power Levels and Surface Absorption Coefficients in Multi-Source Industrial Buildings by Using a Simplified Diffusion Model - SEQUEIRA, Martín E.; CORTÍNEZ, Víctor H. (Archives of Acoustics, 2018)
This article deals with the identification of sound powers and absorption surface coefficients in multisource industrial buildings from the knowledge of the sound pressure levels (SPLs) at several monitoring points. This inverse problem is formulated as one of optimisation in which the objective function is the difference between the measured and predicted SPLs. The methodology combines the use of a simplified acoustic diffusion model with the simulated annealing optimisation technique. The former is a recently developed model for estimating the SPLs in a fast and sufficiently accurate form. The low computational cost of the model constitutes the major advantage for the optimisation procedure due to the great number of simulations required. Numerical examples are given to show the efficiency of the proposed approach.